Role And Place of Internal Audit as an Element of the Entity’s Management System - Moldovan, Mirela; Deliu, Angela (The Journal of Accounting and Management, 2022)
Information on the economic and financial activity of any organization is recorded in the separate accounting system. At the same time, the system in question cannot perform its functions efficiently without promoting an internal control, which, being rationally designed and correctly applied, contributes to ensuring the concordance between the recorded data and reality. In this context, many internal and external users may show a lack of trust in the data flows provided, because those who issue it are usually not independent of the economic facts performed, the presentation of financial reports, management decisions, etc. All these circumstances largely and rightly raise certain doubts relevant to the impartiality and objectivity of the separate data flows. Everyday theory and practice perfectly demonstrate that the knowledge by the users of the way of carrying out the economic activity represents an essential requirement of the management. Thus, in order to eliminate the suspicions from the information users, the improvement of the patrimony management method, the organization and the sustainable development of the production activity of the enterprise, it is necessary to organize an internal audit service, as an element of the entity’s management system. For these reasons, in this article the author has tried to explain the role and place of internal audit as an element of the management system of the entity that ultimately contributes to understanding this activity to protect the interests of different categories of information beneficiaries, and to facilitate decision-making management based on profit criteria.